Evaluasi kesesuaian lahan padi pasang surut di Distrik Kamundan Kabupaten Teluk Bintuni - Suca, Marwah L. Ginting; Bachri, Samsul; Tola, Kati Syamsudin Kadang (Fakultas Pertanian Universitas Papua, 2023)
Agricultural activities on tidal marshland are strongly influenced by the tide (rise) and ebb (fall) of sea or river water. This study aims to (1) Determine soil physical and chemical property criteria; (2) Evaluate soil fertility; and (3) Evaluate tidal paddy suitability. The research site is in the tidal lands of Kamundan District of Teluk Bintuni Regency. The method used is a descriptive method with a survey technique. The results of the study were obtained (1) Criteria of physical and chemical properties of the soil has the physical properties of dusty clay. Soil chemical properties are average slightly acidic pH, low C-organic, medium, high, low to moderate N-total, very low to low P-available, very low to low Potassium, very low KTK, and high KB. (2) Soil fertility status is classified as low which is influenced by low values of P-available and Potassium soil. Low p-available soils are present on (river embankments, switchbacks and back bogs) and Low classified soil Potassium is present on river embankments, and (3) The results of land suitability analysis obtained on river embankments have an actual land suitability class of S3Na with limiting factor P-available, Very low Potassium can be upgraded into potential land suitability by performing Phosphate and Potassium fertilization with proper dosages and schedules, addition of organic matter through the use of manure. In the Intermediate and Back Swamp areas obtained the actual land suitability of S3na with a very low Potassium limiting factor can be increased to potential land suitability by performing Potassium fertilization with proper dosage and schedule, addition of organic matter through the use of manure.